2024
DOI: 10.52223/econimpact.2024.6102
|View full text |Cite
|
Sign up to set email alerts
|

Energy, Forests and Environmental Sustainability: A Comparative Analysis of Developed and Developing Economies

Muhammad Ghulam Shabeer,
Farhat Rasul

Abstract: The use of fossil fuels is essential for economic growth, but it also creates environmental hazards that cause 5 million people to die every year. The use of renewable energy is limited because of financial constraints, and there is a need to find ways to decouple fossil fuel consumption and pollution. This study provides a way forward by introducing forest as a moderator. This study has taken data from all countries of the world from 2011 to 2021 and estimated the impact of forests, energy consumption, forest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Rahman et al (2020) highlight a positive relationship between R&D, innovation, high-tech exports, and economic growth across 51 countries from 2001 to 2015, with long-term effects observed in high-income countries. Other scholars who have worked on innovation and technology are (Shabeer & Rasul, 2024b;Wang et al, 2023;Huang et al, 2023;Arshed et al, 2022;Gul et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Rahman et al (2020) highlight a positive relationship between R&D, innovation, high-tech exports, and economic growth across 51 countries from 2001 to 2015, with long-term effects observed in high-income countries. Other scholars who have worked on innovation and technology are (Shabeer & Rasul, 2024b;Wang et al, 2023;Huang et al, 2023;Arshed et al, 2022;Gul et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chaudhry (2011) concluded that countries with strong institutions tend to gain more from trade in terms of growth, while countries with weak institutions face challenges in maximizing the benefits of trade. Institutions and innovation play significant roles in high-tech trade (Shabeer & Rasul, 2024b). Tebaldi (2011) discovered that institutions alone don't directly influence high-tech exports.…”
Section: Institutions and High-tech Exportsmentioning
confidence: 99%
“…By bridging these research gaps and providing a thorough analysis of the intricate interactions between fin-tech, traditional banking, and contextual factors, this study hopes to significantly contribute to the ongoing effort to achieve financial inclusion for all. Policymakers, financial institutions, and fin-tech companies can work together more successfully to develop and execute long-term solutions that close the gap in commercial banking penetration and empower people and communities worldwide by comprehending the complex dynamics at work (Singh et al, 2021;Shabeer & Rasul, 2024b).…”
Section: Vol 13 Issue 1 (March 2024)mentioning
confidence: 99%
“…One of the most important issues is the collection of tax revenue because, despite differences in economic conditions, different nations have different taxation structures. However, many countries share a parallel structure for sales taxes, excise taxes, and customs duties (Baunsgaard & Keen, 2010;Shabeer & Rasul, 2024b).…”
Section: Introductionmentioning
confidence: 99%